EFFECT OF PALM POLLEN,PUMPKIN EXTRACT, NANO FERTILIZER AND THEIR INTERACTIONS WITH WHEAT HERBICIDES - S. H. A. Al-ziady; L. A. Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was aimed to study the effect of the interaction of herbicides and varieties with different types of foliar nutrition in production the highest yield for three wheat varieties. A field experiment was carried out at the College of Agricultural Engineering Sciences - University of Baghdad / Jadiriyah for two seasons, as the seeds of the first season were sown on 13/12/2018 and harvested on 15/5/2019, and the seeds of the second season were sown on 4/12/2019 and harvested on 10/5/2020. The randomized complete block design (RCBD) was used in the arrangement of split plots, the nutrition included the main plots, while the varieties with herbicides treatments occupied the secondary plots with three replications. The treatment of V3H3 was significantly superior in achieving the highest average in the grain yield value 4.75 and 5.10 ton h-1 for the two seasons, respectively. As for the nutrition, treatment F3 gave the highest average in the grain yield amounted to 4.74 and 4.69 ton ha-1 for the two seasons, respectively. It could be concluded that V3H3 the best treatment to compete with the weeds by giving it the highest yield. Also, It is noted that the leaves feeding treatments all led to a significant increases in the yield and some of its components despite the normal fertilization treatment was the best treatment by giving it the highest grain yield and a significant increases in two of the yield components.